The Developmental Sequence and Relations Between Gesture and Spoken Language in Toddlers With Autism Spectrum Disorder. Issue 3 (31st December 2018) - Talbott, Meagan R.; Young, Gregory S.; Munson, Jeff; Estes, Annette; Vismara, Laurie A.; Rogers, Sally J.
Abstract : In typical development, gestures precede and predict language development. This study examines the developmental sequence of expressive communication and relations between specific gestural and language milestones in toddlers with autism spectrum disorder (ASD), who demonstrate marked difficulty with gesture production and language. Communication skills across five stages (gestures, word approximations, first words, gesture‐word combinations, and two‐word combinations) were assessed monthly by blind raters for toddlers with ASD participating in an randomized control trial of parent‐mediated treatment ( N = 42, 12–30 months). Findings revealed that toddlers acquired skills following a reliable (vs. idiosyncratic) sequence and the majority of toddlers combined gestures with words before combining words in speech, but in contrast to the pattern observed in typical development, a significant subset acquired pointing after first words.